File Compression Application Design Using Half Byte Algorithm - Rizki Manullang; Paska Marto Hasugian (Jurnal Info Sains : Informatika dan Sains, 2021)
The need for large data storage capacity seems increasingly important. This need is caused by the data that must be stored more and more. The storage is not allocated in one place only. But they will also store data or files elsewhere as data backups. How much storage capacity must be provided to hold all the data. Half Byte algorithm is one of the data compression algorithms. The Half Byte algorithm utilizes four left bits that are often the same sequentially especially text files. When the first four bits of the character are received in a row seven or more times, the algorithm compresses the data with marker bits, then the first character of the same four-bit series is followed by the last four-bit pair of the next series